دور فريق الهندسة المتزامنة في تحسين جودة المنتجات - داود, غسان قاسم; نوري, حيدر شاكر (Journal of Economics and Administrative Sciences, 2008)
Concurrent Engineering approved that it is  distinguished technology efficiency as it reflect its affection on international great companies . Its becomes vital field connected with  its  ability  to develop  the products directly, as well as, its concentration  on  all local and international competition  which  need  to  research  and expanded  This  study  deals  with (concurrent  engineering)  subject  in    (Dyala  State  Company  for  Electrical  Industry) , to  bring  the  benefits  of   this  technology  to  develop  the  company  goods  by using of questionnaire as method to data collection for Sample of employees including high administrations managers  and  department management in the company to reach of outcomes to reinforce roles of concurrent engineering to products quality.